(untitled) (INNOVATIVE ECONOMY, 2026)
Bezsmertna O.V. MODERN INFORMATION TECHNOLOGIES IN THE PLANNING SYSTEM FOR THE USE OF ENTERPRISE’S MATERIAL RESOURCES Purpose. The aim of the article is to substantiate the role of modern information technologies in the planning system for the use of enterprise’s material resources and analysis of their impact on the optimization of inventories, automation of management processes, increasing production efficiency and ensuring timely adoption of management decisions. Methodology of research. General scientific and special methods were used in the process of research: analysis and synthesis - to generalize theoretical approaches to the use of information technologies in the enterprise’s resource planning system; systemic approach - to consider the process of material resource management as an integrated system of interconnected elements; structural and functional analysis - to determine the functions of modern information systems in the processes of supply, accounting and control of resources; graphical method - to visualize the relationships between information technologies and material resource utilization efficiency; comparative analysis - to characterize modern ERP-, MRP-, SCM- and CRM-systems. Findings. The conducted research showed that modern information technologies provide effective planning and management of the use of material resources of the enterprise. It was established that ERP systems contribute to the integration of production, logistics, financial and management processes in a single information environment. MRP and MRP II systems provide accurate planning of material needs and optimization of inventories, and SCM systems increase the efficiency of supply chain management. The role of CRM systems in demand forecasting and the influence of cloud technologies and Big Data on the efficiency of information processing and support for management decisions were studied. It was determined that the digitalization of material flow management processes, automation of warehouse accounting, the use of RFID technologies and electronic document management contribute to reducing costs and increasing the efficiency of the enterprise’s production activities. Originality. The substantiation of the role of modern information technologies in the system of planning for the use of enterprise’s material resources in the conditions of digitalization of management processes has been further developed. The functional capabilities of modern ERP, MRP, SCM and CRM systems have been systematized and their impact on the optimization of material flows, increasing the efficiency of inventory management, automating accounting processes and ensuring the coordination of management decisions in the system of resource provision of an enterprise has been determined. Practical value. The research results can be used by enterprises to improve the material resources planning system, increase the efficiency of inventory management, automate accounting and control of material flows. The practical significance lies in the possibility of implementing modern ERP, MRP and SCM systems, digital platforms and predictive analytics to ensure timely supply of resources, reduce operating costs and increase production efficiency. The results also contribute to the development of a single information environment of the enterprise and improve the quality of management decisions. Key words: information technologies, resource planning, ERP systems, MRP systems, SCM systems, digitalization of management, material resources, accounting automation, Big Data, resource utilization efficiency.